The Sultan Qaboos Grand Mosque - Damluji, Salma Samar; Williams, Alan (Apex Press and Publishing, 2007)
Keywords: Architecture – Oman; sultan d'Oman) – Monuments

القيم في فقه العمران : دراسة للتراث العماني - المقيمي, أسعد بن حمود; الخوالدي, البراء بن خالد (2025)
Keywords: Architecture – Oman

Modern Architectures vs ‘Pre-Modern’ Ḥārāt: Architecture Against the Tribes in Oman - Delitz, Heike (Mudbrick Settlements of the Oman Peninsula Inhabited - Abandoned - Re(dis)covered, 2025)
Keywords: Architecture – Oman; Archéologie – Oman; Urbanisme – Oman

#Mudbrick #Oman: On the Tourist Perception of Abandoned Ḥārāt Architecture - Kanditt, Josephine; Schmidt-Lux, Thomas (Mudbrick Settlements of the Oman Peninsula Inhabited - Abandoned - Re(dis)covered, 2025)
Keywords: Architecture – Oman; Archéologie – Oman; Tourisme – Oman; Urbanisme – Oman

Harat Al ʿAqr in Nizwa and Three Artistic Traditions - Bandyopadhyay, Soumyen; Briguglio, Claudia (Mudbrick Settlements of the Oman Peninsula Inhabited - Abandoned - Re(dis)covered, 2025)
Keywords: Architecture – Oman; Archéologie – Oman; Urbanisme – Oman

Reclaimed, Rediscovered or Reinvented – The Changing Perceptions of Ḥārāt since the Omani Nahḍa - Mershen, Birgit (Mudbrick Settlements of the Oman Peninsula Inhabited - Abandoned - Re(dis)covered, 2025)
Keywords: Architecture – Oman; Archéologie – Oman; Urbanisme – Oman

Documentation of Omani Traditional Settlements (Ḥārāt): Reality and Aspirations - Mahrooqi, Ali Bin Hamood al- (Mudbrick Settlements of the Oman Peninsula Inhabited - Abandoned - Re(dis)covered, 2025)
Keywords: Architecture – Oman; Archéologie – Oman; Urbanisme – Oman

Memory and Belonging in the Bat Oasis, Oman - Young, Ruth; Brooks, Alasdair (Mudbrick Settlements of the Oman Peninsula Inhabited - Abandoned - Re(dis)covered, 2025)
Keywords: Architecture – Oman; Archéologie – Oman; Urbanisme – Oman

Life Histories of Mudbrick Settlements in Central Oman - Döpper, Stephanie; Biezeveld, Irini (Mudbrick Settlements of the Oman Peninsula Inhabited - Abandoned - Re(dis)covered, 2025)
Keywords: Architecture – Oman; Archéologie – Oman; Urbanisme – Oman

Mudbrick Settlements of the Oman Peninsula Inhabited - Abandoned - Re(dis)covered - Döpper, Stephanie; Mershen, Birgit; Kanditt, Josephine; Biezeveld, Irini; Schmidt-Lux, Thomas (Sidestone Press, 2025)
Caught between the poles of remembering and forgetting, glorification and neglect, the abandoned mudbrick settlements (ḥārāt) of Oman are a vital object of conflicting processes of interpretation and negotiation. Adopting a diachronic perspective, the multi-disciplinary book’s chapters examine their past, present and future. The book presents approaches and results of archaeological, ethnographic, historical and sociological research on abandoned ḥārāt. Oman’s landscape is dotted with abandoned mudbrick settlements and quarters, known as ḥārāt, either isolated in the countryside or surrounded by vibrant, modern urban centres. Most of them were abandoned during the economic upturn and opening of the country after Sultan Qaboos bin Said came to power in 1970. People’s move from traditional mudbrick to modern concrete houses led to the deterioration and decay of the physical substance of the mudbrick buildings. In the face of these conditions, various Omani and international actors have repeatedly warned against the uncontrolled loss of this valuable cultural heritage. The former inhabitants of the mudbrick houses and their descendants have also repeatedly emphasised their emotional attachment to these abandoned places and their personal significance to them. At the same time, others, especially tourists, have glorified the dilapidated state of the ruins as an aesthetically beautiful backdrop for a romanticised vision of the past. This was the starting point for the interdisciplinary research project “The abandoned mudbrick settlements of central Oman: Between romanticisation and neglect”, funded by the Gerda Henkel Foundation as part of the “Lost Cities” programme between 2020 and 2022, and conducted by the editors of the present volume. It constitutes the proceedings of the closing conference of the project, in which team members present their results and leading experts give their input on inhabited, abandoned and re(dis)covered mudbrick settlements in the Sultanate of Oman.
Keywords: Architecture – Oman; Archéologie – Oman; Urbanisme – Oman

The Omani Mosques and the Mosque Unearthed by the Italian Archaeological Mission at Ẓafār/al-Balīd, in the Dhofar Region - Giunta, Roberta (Annali dell'Istituto Universitario Orientale di Napoli, 2024)
Abstract The article provides a brief overview of the Omani mosques that the Italian archaeologist P.M. Costa classified into two groups in the 1970s based on their floor plans, architectural features, and decorative elements: those from the northern inland regions and those situated along the Indian Ocean coast. A new mosque recently brought to light by the Italian Archaeological Mission to al-Balīd of the University of Naples L’Orientale belongs to this second group.
Keywords: Architecture – Oman; Archéologie – Oman

A blend of local traditions and foreign influences. Art and architecture in oman - Mols, Luitgard (Oman: catalogue created for the oman exhibition in de nieuwe kerk, amsterdam, from 17 october 2009 to 18 april 2010, 2009)
Keywords: Architecture – Oman

Traditional architecture of forts and mosques in oman - Tamimi, Ahmed Mohammad al- (Oman: catalogue created for the oman exhibition in de nieuwe kerk, amsterdam, from 17 october 2009 to 18 april 2010, 2009)
Keywords: Architecture – Oman

Documentation and heritage management plan for Bahla: Harat Al-Aqr - Oman Committee for the Registration and Protection of Historic Building Clusters (Ministry of Heritage and Culture, 2014)
Keywords: Architecture – Oman; Monuments – conservation – Oman

Documentation and heritage management plan for Bidbid: Harat Fanja - Oman Committee for the Registration and Protection of Historic Building Clusters (Ministry of Heritage and Culture, 2014)
Keywords: Architecture – Oman; Monuments – conservation – Oman

Documentation and heritage management plan for Birkat al-Mawz: Harat As-Saybani - Oman Committee for the Registration and Protection of Historic Building Clusters (Ministry of Heritage and Culture, 2014)
Keywords: Architecture – Oman; Monuments – conservation – Oman

Documentation and heritage management plan for Ibri: Harat As-Sulayf - Oman Committee for the Registration and Protection of Historic Building Clusters (Ministry of Heritage and Culture, 2014)
Keywords: Architecture – Oman; Monuments – conservation – Oman

Documentation and heritage management plan for Izki: Harat Al-Yemen - Oman Committee for the Registration and Protection of Historic Building Clusters (Ministry of Heritage and Culture, 2014)
Keywords: Architecture – Oman; Monuments – conservation – Oman

‘Architectural Design for Procuring Thermal Comfort’: Hassan Fathy, Nubia, and Desert Building - Reynolds, Nancy Y. (International Journal of Islamic Architecture, 2024)
As part of an indigenous building movement in the Global South, the United Nations published two books by Egyptian architect Hassan Fathy (1900–89): one on building ‘for the poor’ and the other on passive cooling in vernacular architecture from hot environments. Using his correspondence, reports, designs, published writings, and built forms, this article tracks Fathy’s changing use of a crucial technique, mud-brick vaulting, that he learned in Nubia, an area of Egypt’s arid south largely destroyed by dams in the twentieth century. I show how Fathy mined Nubia rhetorically and materially to use, and later attempt to copyright, its residents’ ‘instinctive’ skills for living in hot arid lands. Over time, Fathy’s appropriations helped to transform Nubia’s vernacular morphology into a universal commons of desert and ‘Islamic’ forms, which enabled him to expand the geographic scope of his practice into the Arabian Peninsula in Oman and Saudi Arabia and into the southwestern United States.
Keywords: Architecture – Oman

Mutrah Old Market, Oman: Analysis to Enhance a Living Heritage Site - Amer, Mohamed (Tangible and Intangible Heritage in the Age of Globalisation, 2024)
Mohamed Amer examines the tangible and intangible heritage characteristics of the traditional market of Mutrah in Oman’s capital city of Muscat. He assesses its interactive historic, architectural, urban, social, economic and cultural values alongside their managerial features, in order to identify practical measures for the enhancement of this living cultural heritage, the effective preservation of Omani cultural identity, avenues for local socio-economic empowerment and sustainable cultural tourism. Here, Strengths, Weaknesses, Opportunities and Threats (SWOT) analyses brought to light the internal and external factors that are favourable to achieving these objectives.
Keywords: Architecture – Oman

Häuser bewohnen, mit Häusern leben. Praxistheoretische Überlegungen zu Transformationsprozessen der omanischen Lehmziegelarchitektur (anhand von Fallbeispielen) - Kanditt, Josephine; Schmidt-Lux, Thomas (2022)
Keywords: Architecture – Oman

Talking about Mud: Current discourses on harat architecture in Oman - Schmidt-Lux, Thomas; Kanditt, Josephine (2020)
Keywords: Architecture – Oman

An Architecture of shura: Communal organisation and institutions and their spatio-material correlates in harat of Inner Oman - Mershen, Birgit (2020)
Keywords: Architecture – Oman

The Formation and Influence of the Military Architecture in Oman During Al-Ya'ariba Period (1034-1162 Ah/1624–1749 Ad) - Benkari, Naïma (Journal of Islamic Architecture, 2021)
Despite its richness, the research corpus published about Islamic architecture presents some discontinuities in the knowledge of the architecture in the lands ruled by Muslims. Similarly, the dynamics of influence that might have operated between the "monumental" architecture in these lands and their popular architectures are insufficiently addressed. Moreover, the material culture related to the Islamic civilization is almost exclusively studied as a product that has stopped evolving. The architecture produced during Al-Ya'ariba (Al- Ya'rubi) Imamate (1624-1749) is an instance of these understudied topics in the history of Islamic architecture. This research argues that Al-Ya'rubi Imamate is not only an important chapter in the history of Oman, the Arabian Peninsula, Indian Ocean, and Eastern Africa, but also the architecture of this period has created the identity of Omani architecture as we know it today. Nonetheless, there is no architectural production in this era both in the major references and scientific publications of Islamic architecture in the 17th and 18th centuries. Through field research, comparative analysis, and literature review of the history of Omani architecture, especially in the 17th -18th centuries, this research examines the military architecture in Oman during Al-Ya'ariba Imamate including its reference, and its influence on other architectures. It is a contribution to the scientific endeavour to address this specific architectural typology from the perspective of its mechanism of (trans) formation and its continuity of forms until the contemporary architecture of Oman.
Keywords: Architecture – Oman

Design and Performance Comparison of Two Patterns of Wind-catcher for a Semi-enclosed Courtyard - Benkari, Naïma; Fazil, Ijaz; Husain, Afzal (International Journal of Mechanical Engineering and Robotics Research, 2017)
Keywords: Architecture – Oman

Archaeological site of Bat-Oman, management and public perception: Community involvement in archaeological heritage management and planning - Benkari, Naïma (Journal of Cultural Heritage Management and Sustainable Development, 2018)
Purpose The purpose of this paper is to present the physical context of the necropolis of Bat, look at its management by the Omani Ministry of Heritage and Culture (MHC), and discusse the challenges it is facing. It will also shed light on how the site of Bat is perceived by the local community and visitors. Design/methodology/approach The archaeological complex of Bat, al-Khutm, and al-Ayn was listed by the UNESCO as a world heritage site in 1988. Despite this classification, relatively little attention has been given to the management of this site. The author conducted interviews with representatives of the MHC in order to understand how this site is being managed, and the author uploaded an online public questionnaire to learn how the population is being educated about the importance of this heritage. Findings The results of this investigation revealed a surprisingly high level of public awareness about the importance of this site to the country socially, and economically. In spite of this awareness, the site is not visited frequently because it is not adequately equipped: a situation that was clearly outlined by the respondents. Suggestions were proposed in order to better integrate this site into the local development plans and the socio-economic growth of the whole region. Originality/value The originality of this research is that it took the site of investigation an archaeological site listed by the UNESCO for its outstanding universal value and contrary to what is expected, this site was “forgotten” in all development and management plans executed by the local and central government for almost two decades. It is also the first research about a site in Oman to address such issues and use these methods.
Keywords: Architecture – Oman

The built heritage as a resource for architectural education: documentation of the vernacular settlements and architecture in Oman - Benkari, Naïma (Journal of Cultural Heritage Management and Sustainable Development, 2024)
Keywords: Architecture – Oman

What Is the Purpose of the Chinese Phoenix in Oman’s Mosques? - Hajri, Hilal al- (The Silk Roads between China and Oman: Networks of Communication and Transmission of Ibadi Knowledge, 2021)
Keywords: Architecture – Oman

Architecture and Building Techniques at the Early Bronze Age site of HD-6, Ra’s al-Hadd, Sultanate of Oman - Azzara, Valentina (2012)
Keywords: Architecture – Oman

Muscat: Rethinking Its Heritage - Amrousi, Mohamed El (Traditional Dwellings and Settlements Review, 2006)
Keywords: Architecture – Oman

The Architecture of Oman in its future perspective - الدملوجي, سلمى سمر (2021)
جامعة سلطان قبوس
Keywords: Architecture – Oman

Symmetry Groups of Islamic Patterns at the Sultan Qaboos Grand Mosque - Laigo, Glenn R.; GebreYohannes, Haftamu Menker; Khamisi, Fahad Mohammed Humaid Al (Proceedings of Bridges 2014: Mathematics, Music, Art, Architecture, Culture, 2014)
In this paper, we analyze Islamic patterns found at the Sultan Qaboos Grand Mosque in Muscat, Oman. We use group theory to analyze these patterns. In particular, we consider dihedral, frieze, and wallpaper groups as possible symmetry groups of the patterns.
Keywords: Architecture – Oman

Notes on the Ibadi religious architecture: a comparative study of the mosques in Mzab, Djerba, and Oman - Benkari, Naïma (Proceedings of 2nd international islamic heritage conference (ishec 2017), 2017)
Keywords: Architecture – Djerba; Architecture – Mzab; Architecture – Oman

The defensive vernacular settlements in oman, a contextual study - Benkari, Naïma (International Journal of Heritage Architecture, 2017)
Keywords: Architecture – Oman

The Architecture of Omani Oases: a Mirror of Social Structures - Korn, Lorenz (Oases of Oman : Livelihood Systems at the Crossroads, 2010)
Keywords: Architecture – Oman

Mosquées ibadites et islam standard au sultanat d’Oman - Prevost, Virginie (Acta Orientalia Belgica, 2011)
Keywords: Architecture – Oman; Monuments – Oman

The poetics of Oman’s traditional architecture: towards an aesthetic interpretation - Kite, Stephen (Journal of Oman Studies, 2002)
Keywords: Architecture – Oman

The great mosque of Qalhāt - Costa, Paolo M. (Journal of Oman Studies, 2002)
Keywords: Architecture – Oman

Ḥārat al-Bilād (Manaḥ): tribal pattern, settlement structure and architecture - Bandyopadhyay, Soumyen (Journal of Oman Studies, 2004)
Keywords: Architecture – Oman

Qalʿat Nizwà. Namūdhaj li’l-ʿImāra al-ʿAskariyya fī ʿUmān, 1650-1679 - Ṭarāwina, Khalaf Fāris al-; ʿAlawī, Badr b. Hilāl Khalīfa al- (Aʿmāl al-Multaqà al-ʿIlmi al-awwal ḥawla Turāth Salṭanat ʿUmān al-Shaqīqa Qadīman wa-Ḥadīthan, 2002)
Keywords: Architecture – Oman

Conflation of celestial and physical topographies in the Omani decorated miḥrāb - Bandyopadhyay, Soumyen (Proceedings of the Seminar for Arabian Studies, 2010)
Thispaperdiscussestheroleandoverlappingmeaningoftwokeythemespersistenwt ithintheOmanidecorativetraditions,tars anddatepalms,byfocusingonthedecoratedprayerniches(mahãrfbs,g.mihrãbo) fOman.Italso addressesthecloseconnection betweenconceptionosftopographiynOmanicultureandthearticulatioonfthresholdbs,othsacredanddomesticT. hepaperargues thatan attempttoconnectthecelestialandphysicaltopographicconceptiontshatis attheheartofthecomplexwaterdistribution strategyoftheaflãjirrigatiosnystemalso prevailsin themihrãbT. he Ibadï artisanof Omanintegraterdepresentatioonfsboth continuouasndinstantaneoutismeemployintgheendlessknotandstellarmotifsE.mphasizingthesacrednatureoftimeandlightas divineattributeosressenceofGod,themihrãbsoughttorepresenatcelestialtopographyw,hichwas madepossiblethroughIbadï analogicalinterpretatioonfsanthropomorphiisnmtheQurDanandan expandinginfluencoefmysticismamongstOmanischolars. Omanimihrãband doordecorationshowsa close affinitbyetweenstellarand date-palmrepresentationtsh,elatteralso heldin sacredesteeminOman.Theaflãjirrigatiosnystemoncedependedsignificantolyn thepositionofstarsinthenightskytoensure thedistributioonfwaterT. heinterchangeabrlepresentatiosunggestsa conflatioonftheterrestritaolpographoyftheoasisandthe celestialtopographyTh. ehorizonmediatedthisrelationshipac,tingas a thresholtdhroughwhichthecelestialbodieshadtopassto be meaningfulalyssociatedwiththeterrestritaolpographyA.ppearingas woventapestrieosrboundedspatialrepresentationbso,th themihrãbandtheOmanidoorwaydecorationmarka thresholidnthesacredandsecularpassage.
Keywords: Architecture – Oman

The distinctive typology of central Omani mosques: its nature and antecedents - Bandyopadhyay, Soumyen; Sibley, Magda (Proceedings of the Seminar for Arabian Studies, 2003)
Keywords: Architecture – Oman

From the twilight of cultural memory: the būmah in the mosques of central Oman - Bandyopadhyay, Soumyen (Proceedings of the Seminar for Arabian Studies, 2000)
Keywords: Architecture – Oman

Diversity in unity: an analysis of the settlement structure of Ḥārat al-ʿAqr, Nizwā (Oman) - Bandyopadhyay, Soumyen (Proceedings of the Seminar for Arabian Studies, 2005)
Keywords: Architecture – Oman

Historic mosques and shrines of Oman - Costa, Paolo M.; Baldissera, Eros (Archaeopress, 2001)
Keywords: Architecture – Oman

Works of architectural restoration in Oman - Biancifiori, Maria Antonietta (Ed. De Luca, 2006)
The work of the architect Giuseppe Biancifiori (1942-1991).
Keywords: Architecture – Oman

Manah: an Omani oasis, an Arabian legacy ; architecture and social history of an Omani settlement - Bandyopadhyay, Soumyen (Liverpool Univ. Press, 2011)
Keywords: Architecture – Oman